Electron Beam Radiation as a Safe Method for the Sterilization of Aceclofenac and Diclofenac-The Usefulness of EPR and 1H-NMR Methods in Determination of Molecular Structure and Dynamics - Marcin Janiaczyk; Anna Jelińska; Aneta Woźniak-Braszak; Paweł Bilski; Maria Popielarz-Brzezińska; Magdalena Wachowiak; Mikołaj Baranowski; Szymon Tomczak; Magdalena Ogrodowczyk (MDPI AG, 2022)
Diclofenac (DC) [2-(2,6-Dichloroanilino)phenyl]acetic acid,) and aceclofenac (AC) 2-[2-[2-[(2,6-dichlorophenyl)amino]phenyl]acetyl]oxyacetic acid in substantia were subjected to ionizing radiation in the form of a beam of high-energy electrons from an accelerator in a standard sterilization dose of 25 kGy and higher radiation doses (50-400 kGy). We characterized non-irradiated and irradiated samples of DC and AC by using the following methods: organoleptic analysis (color, form), spectroscopic (IR, NMR, EPR), chromatographic (HPLC), and others (microscopic analysis, capillary melting point measurement, differential scanning calorimetry (DSC)). It was found that a absorbed dose of 50 kGy causes a change in the color of AC and DC from white to cream-like, which deepens with increasing radiation dose. No significant changes in the FT-IR spectra were observed, while no additional peaks were observed in the chromatograms, indicating emerging radio-degradation products (25 kGy). The melting point determined by the capillary method was 153.0 °C for AC and 291.0 °C for DC. After irradiation with the dose of 25 kGy for AC, it did not change, for DC it decreased by 0.5 °C, while for the dose of 400 kGy it was 151.0 °C and 286.0 °C for AC and DC, respectively. Both NSAIDs exhibit high radiation stability for typical sterilization doses of 25-50 kGy and are likely to be sterilized with radiation at a dose of 25 kGy. The influence of irradiation on changes in molecular dynamics and structure has been observed by 1H-NMR and EPR studies. This study aimed to determine the radiation stability of DC and AC by spectrophotometric, thermal and chromatographic methods. A standard dose of irradiation (25 kGy) was used to confirm the possibility of using this dose to obtain a sterile form of both NSAIDs. Higher doses of radiation (50-400 kGy) have been performed to explain the changes in DC and AC after sterilization.